1997
DOI: 10.1021/ie960338v
|View full text |Cite
|
Sign up to set email alerts
|

Cs+ Ion Exchange Kinetics in Complex Electrolyte Solutions Using Hydrous Crystalline Silicotitanates

Abstract: TAM-5 is a hydrous crystalline sodium silicotitanate inorganic ion exchanger with a high selectivity for Cs + . The kinetics of Cs + -Na + ion exchange using TAM-5 in multicomponent electrolyte solutions were determined using batch experiments. For the powder, which is composed of crystals, a single-phase, homogeneous model fit the data best. For the granules, which were prepared from the powder, a two-phase, heterogeneous model resulted in an excellent fit of the data. Macropore and crystal diffusivities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…However, because of the complexity of the model, only one diffusion resistance (either the micropore or macropore resistance) is considered, thus simplifying the modeling [5]. For example, it has been demonstrated that a two-phase homogeneous model (TPHDM) is sufficient for predicting the adsorption behaviors of zeolites toward various metal ions [5,12,13], assuming that (i) the metal ion concentration in the pore liquid is in instantaneous equilibrium with that on the solid surface, and (ii) the diffusion resistance in the micropores is negligible. ETS-10, a zeolitic material [14] constituted from SiO 4 tetrahedra and TiO 6 octahedra, possesses a high cation-exchange capacity [15,16] because of the presence of tetravalent Ti in an octacoordinated state, which generates two negative charges balanced by alkali cations [17], namely Na + and K + .…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the complexity of the model, only one diffusion resistance (either the micropore or macropore resistance) is considered, thus simplifying the modeling [5]. For example, it has been demonstrated that a two-phase homogeneous model (TPHDM) is sufficient for predicting the adsorption behaviors of zeolites toward various metal ions [5,12,13], assuming that (i) the metal ion concentration in the pore liquid is in instantaneous equilibrium with that on the solid surface, and (ii) the diffusion resistance in the micropores is negligible. ETS-10, a zeolitic material [14] constituted from SiO 4 tetrahedra and TiO 6 octahedra, possesses a high cation-exchange capacity [15,16] because of the presence of tetravalent Ti in an octacoordinated state, which generates two negative charges balanced by alkali cations [17], namely Na + and K + .…”
Section: Introductionmentioning
confidence: 99%
“…Ž . In previous studies Gu et al, 1997;Huckman et al, 1999 , batch kinetic experiments were employed to estimate diffusion parameters in IE-911, which were later used to predict column performance. Since such data were not available for the SRS waste, a series of column experiments conducted at Ž .…”
Section: Equilibriummentioning
confidence: 99%
“…Such a particle is classified as having a bidisperse pore structure. Extensive work has been published regarding the modeling of such particles, and summaries can be found in Gu et al, Ruthven, Robinson et al, DePaoli and Perona, and Huckman et al…”
Section: Modeling Equationsmentioning
confidence: 99%
“…In recent years, much research has focused on developing materials and technologies for the remediation of these wastes. Anthony et al reported the synthesis of a crystalline silicotitanate, labeled TAM-5, which proved to be a selective ion-exchange material for removing the radioactive Cs and Sr from these waste. Several studies have been conducted to determine the equilibrium behavior of the material and its diffusion characteristics. , The industrial application of UOP IONSIV IE-911, the commercial, engineered form of TAM-5, is proposed to be in a continuous-flow arrangement through a series of fixed-bed columns. The objective of this study will be to present a mathematical model which will simulate the performance of the IE-911 granules in a fixed-bed column.…”
Section: Introductionmentioning
confidence: 99%